Online Learning and Academic Performance of Bachelor of Physical Education Students - Gio L. Ledesma; Karen D. Lampedario; Julius D. Pequierda; Vivencio L. Calixtro (Indonesian Journal of Educational Research and Technology, 2021)
This study aimed to find out the relationship between the level of online learning and the academic performance of bachelor of physical education students. The light of this study was to determine students’ level of online learning, evaluate students’ academic performance (in terms of satisfaction, students-instructors interaction, and instructors’ performance), and introduce a new framework to increase students’ satisfaction in learning online. The finding shows that level of online learning in the program is moderate. Students’ academic performance in terms of students’ satisfaction is moderately satisfactory, students-instructors interaction is to a greater extent and instructors’ performance was effective. The level of online learning was not significantly related to students’ satisfaction, and the level of online learning was significantly related to students-instructors interaction and instructors' performance. Based on the findings, interaction with instructors and instructors’ effectiveness in operating online classes affects the learning experiences and performance of students. This research can contribute to the development of the online learning process since it provides information about the status of students upon learning online.